(untitled) (Revista de Ciências Agroveterinárias, 2013)
Canine babesiosis is a tick-borne disease caused by Babesia gibsoni and Babesia canis, comprising of the subspecies B. canis vogeli, B. canis canis and B. canis rossi. These species and subspecies have distinct tick vectors and display distinct pathogenic variables, which may influence the clinical syndromes exhibited by affected animals, besides factors inherent to the infected dog. These morphological, epidemiological and pathogenetic differences of the agents have contributed to variations in the distribution and clinical presentation of the disorder. Therefore, this review aims to expose the etiological, epidemiological, immunological and clinicalpathological features, as well as the methods available for diagnosis of canine babesiosis.